Of some approaches to the personalized user interface organization in automated systems - Furtat, Yu.O.; Diachuk, O.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2014)
In modern automated systems, users are often facing the problem of information overload due to the ever increasing amounts of information to be processed in a short time. Working in these conditions affects the quality of users performing their functions in the system and the reliability of the systems themselves. In the article different existing approaches to solving this problem are described and analyzed, which are based on the idea of creating customized tools for users work with information. On the basis of these solutions a complex methodology of information representation and storage forms personalization is suggested, as well as software architecture based on it. У сучасних автоматизованих системах користувачі часто стикаються з проблемою інформаційного перевантаження через постійно зростаючі обсяги інформації, що вимагає обробки за короткий час. Робота в таких умовах негативно позначається на якості виконання користувачами їх функцій в системі і на надійності самих систем. У статті розглянуто та проаналізовано різні підходи до вирішення цієї проблеми, в основі яких лежить ідея створення персоналізованих засобів роботи користувачів з інформацією. На основі розглянутих рішень пропонується методика комплексної персоналізації форм представлення і зберігання інформації в системі, а також архітектура заснованих на ній програмних засобів.